Relationship Between Sharia-Based Accounting, Accountability, and Credibility - Khakim, M. Azizul (Universitas Syiah Kuala, 2023)
Abstract: In the development of the accounting profession, many methods and ways have been found by experts in maximizing the duties of accounting in providing information to stakeholders. Sharia also appears to have the same vision and mission, so that the quality of performance can be maximized. Sharia accounting comes with the addition of sharia concepts in it. So that the essence of Accounting and Islamic Sciences blend into one unit in forming a good synergy. The basis of sharia values is a strong basis for accounting quality in terms of accountability and credibility. these two concepts are very important because the quality that accountants provide is closely related to these two terms. In this study, researchers will provide conclusions on how the relationship of the three parts in shaping the quality of accounting applied by entities. Sharia Accounting, Accountability, Credibility, Relationship,